Lifestyle Interventions and Prevention of Suicide - Berardelli, Isabella; Corigliano, Valentina; Hawkins, Michael; Comparelli, Anna; Erbuto, Denise; Pompili, Maurizio (Frontiers in Psychiatry, 2018)
Over the past years, there has been a growing interest in the association between lifestyle psychosocial interventions, severe mental illness and suicide risk. Patients with severe mental disorders have higher mortality rates, poor health states and higher suicide risk compared to the general population. Lifestyle behaviors are amenable to change through the adoption of specific psychosocial interventions, and several approaches have been promoted. The current article provides a comprehensive review of the literature on lifestyle interventions, mental health and suicide risk in the general population and in patients with psychiatric disorders. For this purpose, we investigated lifestyle behaviors and lifestyle interventions in three different age groups: adolescents, young adults and the elderly. Several lifestyle behaviors including cigarette smoking, alcohol use and sedentary lifestyle are associated with suicide risk in all age groups. In adolescents, growing attention has emerged on the association between suicide risk and internet addiction, cyberbullying and scholastic and family difficulties. In adults, psychiatric symptoms, substance and alcohol abuse, weight and occupational difficulties seems to have a significant role in suicide risk. Finally, in the elderly, the presence of an organic disease and poor social support are associated with an increased risk of suicide attempt. Several factors may explain the association between lifestyle behaviors and suicide. First, many studies have reported that some lifestyle behaviors and its consequences (sedentary lifestyle, cigarette smoking underweight, obesity) are associated with cardiometabolic risk factors and with poor mental health. Second, several lifestyle behaviors may encourage social isolation, limiting the development of social networks and remove individuals from social interactions; increasing their risk of mental health problems and suicide.